The Effect of Natural Plant Growth Regulator Concentration of Indian Red Onions on the Growth of Euphorbia (Euphorbia geroldii) Flowers - Mahfudhah, Dzikra Nasyaya; Anggarani, Mirwa Adiprahara (Jurnal Pijar Mipa, 2024)
The euphorbia flower (euphorbia geroldii), widely used by the public as an ornamental plant because of its visual beauty, has an aesthetic function and health benefits that still need to be researched. The euphorbia genus has antimicrobial, antioxidant, and antidiabetic activity, which comes from its abundant terpenoid compounds, flavonoids, and other phytochemical compounds. Due to these high benefits, optimization of cultivation is carried out by adding phytohormones, better known as Growth Regulatory Regulator (PGR), further to increase the quality and quantity of euphorbia flowers so that the economic value will also increase in the realm of the agricultural industry. This research aims to analyze the effect of the natural PGR concentration of red onions (Allium cepa L.) on the growth of euphorbia flowers, including the parameters of the number of flowers on one tree, the time the buds appear, and the duration of flower survival. The research method used was quantitative experimental using a one-factor Randomized Block Design (RBD), namely testing the effect of several variations in PGR concentration (0%, 1%, 3%, 5%, 7%, and 10%) and statistically analyzed using SPSS. The results of the research show that all variations in PGR concentration have a positive effect on all parameters, where the PGR concentration of 10% indicates the highest increase, including the average number of flowers on one tree, which is 13 flowers, the average time for buds to appear is 2.5 times in one week. The average duration of flower survival is 139.5 hours. It can be concluded that the natural PGR of red onions has a positive effect on all parameters, with the highest results shown at a concentration variation of 10%.